MAINTENANCE PERALATAN PRODUKSI DI PONDOK PESANTREN DARUL MUTTAQIN KOTA BATU - Teguh Dwi Widodo; Ari Wahyudi; Rudianto Raharjo; Redi Bintarto; Arif Wahyudiono (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Darul Muttaqin Islamic boarding school product production activities are very dependent on the equipment that supports the production of these products. By increasing the reliability of production equipment, production from Islamic boarding schools will increase so that the economic level can be achieved well. Production equipment whose reliability is maintained by maintenance includes chili sauce making machines, tempe chips making machines, transportation equipment and other workshop equipment. The maintenance process is carried out by starting with mapping damage data for each component of the existing equipment. This data is taken from several sources that are close to or equal to existing treatments. From the existing analysis, several care and maintenance processes need to be carried out on certain parts of the equipment. The problem found by the Darul Mutaqin Islamic boarding school is a lack of knowledge regarding the proper maintenance process. This maintenance is carried out by the students of the Darul Mutaqin Islamic boarding school with direction and supervision from the service team from the Mechanical Engineering department of Brawijaya University. This activity will result in an increase in students' skills in the field of maintenance.